A Revista Veja e as empresas da construção civil (1968-1978) - Rautenberg, Édina (2011)
This study would investigate the speech and the standpoint of the Veja Magazine, of the publishing house Abril, about the civil construction companies during the brazilian dictatorship civil-military, taking as cut out the magazine's first ten years (1968-1978). As delimiting, it was selected three of the main works built in that period and then problematize the Veja s speech about the works and specially about their builders. Thereunto, it was analysed the speech of the magazine about these works: Transamazonica Highway, the Rio-Niteroi Bridge and Itaipu Dam. The dissertation was initiated presenting our study object, the Veja magazine, and it was situated on its political context, where it was created (first chapter), it was through a bibliographic discussion, that situates the formation of the capitalism and the capitalism State in Brazil, also its specificities about the military regime (second chapter). These first two chapters are concentrated on the Volume I. The Volume II supports the core of our research, where we analysed the Veja's viewpoint in relation of the builders and the works analysed. The third chapter is based on discourse analysis and on the Veja s viewpoint about the Transamazonica Highway construction, whose works have started in 1970 by the builders: Camargo Correa, Rabello S/A, EIT, Queiroz Galvão, Mendes Júnior, S. A. Paulista, Paranapanema, and by the Battalions of Engineering and the Army Building (BECs). The fourth chapter worked with the Veja s analysis about the construction of the Presidente Costa e Silva Bridge, popularly known as Rio-Niterói Bridge, whose construction have started in 1969, by the Builder Consortium Guanabara, formed by the companies Camargo Correa, Mendes Junior, Rabello S. A. and Sérgio Marques de Souza. Despite the scarce bibliography about the theme, the chapter tried to present the events that involved the construction of the work, even as analysed how Veja was positioning itself in relation to the work. The fifth chapter analysed the discourse and the Veja s viewpoint about the construction of the Itaipu Hydroelectric Power Plant, whose works have started in 1975. The construction was in charge of two consortia, one was Brazilian and another Paraguayan. The UNICON (Union of Construction Ltd.), Brazilian, formed by the Cetenco Engineering Ltd., CBPO Brazil's Cia Paving and Construction, Camargo Correa, Andrade Guttierrez and Mendes Junior Companies; and CONEMPA (Consortium of Paraguayan Construction Companies), formed by Barrail Hermanos, Cia. General of Construcciones, ECCA. S. A., Ing. Civil Hermanos Baumam, ECOMIPA Emp. Const. Min. Paraguaya e Jimeñez Gaona & Lima Companies. We hope with this work demonstrate the relation of Veja with the dictatorship and also with the civil construction companies (that grew up because of the dictorial policies), demonstrating and questioning these power relations permeating the civil society and the viewpoint of Veja into these relations